MPPT & Power Factor Control for Grid Connected PV Systems with Fuzzy Logic Controllers - Taoufik Laagoubi; Mostafa Bouzi; Mohamed Benchagra (Institute of Advanced Engineering and Science, 2018)
Two fuzzy logic controllers are proposed in this paper to control a three phase inverter for grid connected photovoltaic system. The first controller was used to predict the DC voltage that allows the three phase inverter to track the maximum power point of photovoltaic array under different environmental conditions such as irradiances and temperature. The second was used to control the active power and reactive power injected into the grid in order to inject the maximum active power produced by photovoltaic systems into grid with high efficiency and low total harmonic distortion using the same three phase inverter. The system components are photovoltaic array, DC link voltage, three-phase inverter, inverter control, LC filter, transformer and grid. To verify the effectivnesse of the introdueced system, modeling and simulation are verified in Matlab/Simulink due to its frequent use and its effectiveness.